PENGARUH TEMPERATUR KALSINASI TERHADAP SIFAT MEKANIK MATERIAL SCAFFOLD HIDROKSIAPATIT DARI TULANG KAMBING - Setiawan Eka Prawira; Joko Triyono; Teguh Triyono (Mekanika: Majalah Ilmiah Mekanika, 2019)
In this study, a preliminary study on the preparation of hydroxyapatite (HAp) as bone filler was made from sheep femur bone by calcination method. The femur of the sheep is cut into a form of scaffold with dimensions of 5 mm x 5 mm x 5 mm. The calcination process is performed at four variations of temperature (700oC, 900oC, 1100oC, 1300oC). Characterization of scaffold material done before and after calcination process, it intended to find out the influence and relationship between calcination of temperature on the mechanical properties of SHA material. The results of hardness testing show that the higher calcination temperature then the SHA material hardness value also increased. The optimum hardness value occurs at 1100oC calcination temperature of 38.23±0.985VHN. Meanwhile, high calcination temperature will also decrease the compressive strength of SHA material. The value of the optimum compressive strength is achieved at 1100oC calcination temperature of 2.23±0.249 MPa. The morphology of SHA scaffold was analyzed by Scanning Electronic Microscopy (SEM). The observation of SEM shows the occurrence of porous interconnections in all temperature variations. SEM analysis results show that porous interconnect is formed at all temperature variations with diameter size ± 100-500μm. Very high calcination temperature will give the impact of HAp wall is getting thinner and the porous diameter is getting bigger. Porous interconnection damage is also seen at 1300°C which causes the mechanical properties of SHA to decrease.